Influence of the test specimen diameter on the measurement of electrical resistivity in sands by using laboratory devices - Pregnolato, M. C. [UNESP]; Giacheti, H. L. [UNESP]; Peixoto, A. S.P. [UNESP] (My University, 2016)
Electrical resistivity tests have long been used in geo-environmental site characterization because they provide qualitative data to identify the presence of contaminants in soil. The measurement of soil electrical resistivity is affected by many intervening factors, which are usually studied separately in the laboratory and are important to ensure the correct interpretation of in situ test data. This paper presents the evaluation of the influence of the diameter of test specimens on electrical resistivity measurements of a particulate medium in the laboratory, using two different techniques, copper plates and a resistivity probe. The data were discussed considering Archie's Law, and it indicates that the geometry of test specimen has a greater effect than the measurement technique. The larger test specimen allows more current pathways for electron propagation because electric current travels along the path of least resistance to the passage of electrons. The findings from this research can be used to guide a laboratory test investigation and its data interpretation.
Keywords: Archie Law; Copper plates; Electrical resistivity; Resistivity probe; Site characterization